1868 Ark. Acts 218 - (:unkn) unknown (My University, 1868)
Acts of the General Assembly of Arkansas, § 12: Any person who threatens or draws a pistol, gun, or other deadly weapon upon a sheriff or other officer executing a civil or criminal process shall be deemed guilty of a felony, imprisoned in the penitentiary not less than one nor more than five years.
Keywords: BRANDISHING